Sistema autônomo de navegação para um veículo aéreo não tripulado do tipo quadricoptero - Belusso, Daniel Vinicius (2019)
The technological advancement of the small microcontroller and sensor industry has made unmanned aerial vehicles a reality for corporate as well as the general civilian population. Operation of this type of vehicle may present a number of risks to both third parties and the vehicle itself due to difficulties in handling. The aim was to develop a low-cost quadcopter prototype that can perform user-requested flight missions in an autonomous way that has the ability to dodge obstacles and a visual interface for configuring your flight plan. flight. For this, a Raspberry Pi microcomputer was used in conjunction with a Pixhawk flight controller, which are connected to sensors that are fundamental to the project. The configuration of the flight plan by the user and later the accomplishment of this autonomous mission happens through software developed in python 3 and embedded in the microprocessor.